Fibers of Basalt used to Reinforce Gypsum Products - Olloyor, Muxammadiyev; Zokir, Akhmedov (European Journal of Life Safety and Stability (2660-9630), 2023)
Currently utilized gypsum materials' nano-laboratory testing features are described. Basalt is added to gypsum by pouring it into the dry material and mixing it thoroughly. Therefore, basalt reduces shrinkage deformations and improves the technical properties of dry mixtures.